Chemical and Sensorial Characterization of Tropical Syrah Wines Produced at Different Altitudes in Northeast of Brazil - de Oliveira, J.B.; Egipto, R.; Laureano, O.; de Castro, R.; Pereira, G.E.; Ricardo-da-Silva, J.M. (South African Journal of Enology and Viticulture, 2019)
Over the years, viticulture has expanded to new regions outside the temperate zones, such as Northeast Brazil, India, Thailand, Myanmar, Vietnam, Bangladesh and Venezuela, characterized by the production of tropical wines. It is important for the productive sector to comprehend the effects of grapevine interaction with the characteristics of each new region on wines composition. In this study, the composition of wines of Syrah from two regions with different altitudes in Northeast Brazil were analyzed by different methodologies to characterize chemical compounds as sugar, acids, minerals, phenolics (anthocyanins, flavonols, stilbenes and condensed tannins) and the sensory profile. The wines of the Bahia region (1100 m of altitude) obtained high concentrations for chemical parameters related to color, monomeric anthocyanins, stilbenes and monomeric and oligomeric tannins. Wines of the low altitude region, Pernambuco (350 m of altitude) were characterized by higher concentrations of flavonols (kaempferol, isorhamnetin, quercetin and rutin) and polymerized tannins. The chemical composition of wines from the two studied regions was influenced by altitude. A trend towards higher concentrations in most for phenolic compounds analyzed was observed in wines from the higher altitude region during the two years of study. Regarding the sensory profile, fruity, floral, herbaceous and empyreumatic attributes aromatic obtained highest scores in wines of the 350 m altitude region, the other attributes were dependent on the year of harvest.